Da vontade unificadora do Estado à adaptação da escola pública às realidades locais : o papel dos governadores civis e dos comissários de estudos (anos de 1840-1860) - Silva, Carlos Manique da (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In this paper, it is the author’s purpose to elaborate an overview about the establishment of two institutional figures in the educational field: civil governors and study supervisors. The major interest is to understand if these officials gave an effective contribution to a uniform pedagogical project able to establish national unity in public education.